Versatile carboxymethyl chitin and chitosan nanomaterials: a review. (29th September 2014) - Narayanan, Deepa; Jayakumar, R.; Chennazhi, K. P.
<x xml:space="preserve">Abstract</x> Biocompatibility, biodegradability, and low cost of chitin and chitosan have drawn immense attention in many fields including medicine, bioinspired material science, pharmaceuticals, and agriculture. Their handling and processing are difficult owing to its insolubility in neutral aqueous solution or organic solvents. One of the methods used to improve the solubility characteristics of chitin and chitosan is chemical modification. Introducing a carboxymethyl group is the most advantageous method of increasing the solubility of chitosan at neutral and alkaline pH. Carboxymethyl chitin (CMC) and carboxymethyl chitosan (CMCS) are water soluble derivatives formed by introducing CH2COOH function into the polymer which endows it with better biological properties. The functional group makes CMC/CMCS nanoparticles (NPs) efficient vehicles for the delivery of DNA, proteins, and drugs. This review provides an overview of the characteristics of CMC/CMCS NPs as well as fulfills the task of describing and discussing its important roles primarily in cancer nanomedicine detailing the targeted drug delivery aspect. The application of these NPs in imaging, agriculture, and textiles has also been highlighted. The review also elaborates the advantages of using the CMC and CMCS NPs for drug and gene delivery. WIREs Nanomed Nanobiotechnol 2014, 6:574–598. doi: 10.1002/wnan.1301 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.